Impacto da energia de micro-ondas na sinterização da zircônia odontológica - Luz, Júlio Nogueira [UNESP] (2015)
The objective of this study was to evaluate the impact of the sintering method, conventional and through microwave energy on the microstructural characteristics and mechanical properties of ceramics based on Y- TZP zirconia. The null hypothesis is that sintering is carried out by microwave oven has no effect on the biaxial flexural strength Y- TZP disc, both discs aged by means of a thermo cycler, and in the non- cycled groups. One hundred samples in the form of VIPI Block Zirconn ceramic discs (12 x 1.2 mm) were machined in accordance with ISO 6872 standards for biaxial bending test and were divided into groups according to the method of sintering and thermomechanical aging: Group I: conventional and without mechanical cycling sintering ; Group II : conventional + thermomechanical cycling sintering ; Group III: microwave sintering and without thermomechanical cycling ; Group IV: in microwave sintering + thermomechanical cycling . The specimens were subjected to biaxial bending after sintering for non-cycled groups and after cycling for groups which were submitted to aging ( 1,200,000 cycles, 45 N load and frequency of 2.8 Hz, biaxial, immersed in water 37 °C). Qualitative analysis was performed on samples using a scanning electron microscope and X-ray diffraction samples in eight samples(n = 2) for all groups. For statistical analysis the Weibull modulus (m) was used, and there was no significant difference when compared to cycling, but there was compared the method. The same happened when the analysis of variance (α = 5%) was applied. It follows that sintering protocol performed in this study had no success in dental zirconia sintering and thermal cycling does not affect the microstructure and mechanical properties of Y- TZP